Упростить выражения:

а)(2х-7у)во второй степени+(3х+4у)во второй степени-(зх+у)(зх-у)

б)5(а-4b)(4b+a)+(a-4b)(-4b+a)+(a+4b)во второй степени

2

Ответы и объяснения

2012-03-29T15:13:38+04:00

(2х-7у)^2+(3х+4у)^2-(зх+у)(зх-у)=4х^2-28xу+49y^2+9х^2+24xy+16у^2-9x^2+y^2=

4х^2-4xу+66y^2


5(а-4b)(4b+a)+(a-4b)(-4b+a)+(a+4b)^2=5a^2-80b^2+a^2-8ab+16b^2+a^2+8ab+16b^2=

7a^2-48b^2

Лучший Ответ!
2012-03-29T15:23:05+04:00

а)(2х-7у)во второй степени+(3х+4у)во второй степени-(зх+у)(зх-у)=4х^2-28xy+49y^2+9x^2+24xy+16y^2-(3x^2-y^2)=4x^2-28xy+49y^2+9x^2+24xy+16y^2-3x^2+y^2=10 x^2+66y^2-4xy=x^2+33y^2-2xy

б)5(а-4b)(4b+a)+(a-4b)(-4b+a)+(a+4b)во второй степени=(5a-20b)(4b+a)+(a-4b)(-4b+a)+(a+4b)^2=20ab+5a^2-80b^2-20ba+(-4ab+a^2+16b^2-4ab)+(a+4b)^2=5a^2-80b^2-4ab+a^2+16b^2-4ab+(a+4b)^2=5a^2- 80b^2-4ab+a^2+16b^2-4ab +a^2+8ab+16b^2=7a^2-112b^2=a^2-16b^2=(a-4b)(a+4b)